Kualitas Audit Dalam Pengaruh Penerapan Good Coorporate Governance Terhadap Pencegahan Fraud - Wiwit Pawitri; Suryani, Irma; M.Syahrudin; Aysarah Nuryana (LPPM POLITEKNIK LP3I BANDUNG, 2024)
This study aims to examine the effect of the implementation of good corporate governance on fraud prevention with audit quality as an intervening variable in BUMN companies in 2018-2022. This type of research is quantitative research using secondary data on annual reports and financial reports of BUMN companies listed on the Indonesia Stock Exchange for the period 2018 to 2022. The purposive sampling technique was used to select samples based on criteria so that the selected samples amounted to 15 out of 27 BUMN. Data analysis using Structural Equation Modelling (SEM). SmartPLS software was used as a testing tool. The novelty of this research by adding audit quality that occurs as an intervening variable and using SEM. The results showed that there was no direct influence between gcg implementation on fraud prevention, there was an influence of gcg implementation on audit quality and there was an influence of audit quality on fraud prevention. Audit quality as an intervening variable is able to strengthen the relationship between the effect of gcg implementation on fraud prevention.